Economic structure, education and growth - Ortiz, Carlos Humberto (CIDSE, Centro de Investigaciones y Documentación Socioeconómica, 2021)
This paper analyzes the effects of education on the process of economic diversification in underdeveloped countries. Under the assumption that most technological changes are driven by imitation, we describe how a procese of input-output deepening evolves and how this process increases real income.